2014
DOI: 10.1097/fpc.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

HLA alleles and hypersensitivity to carbamazepine

Abstract: In summary, our meta-analysis showed the presence of HLA alleles contributing toward risk of as well as protection against various CBZ-induced cADRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…In fact, the association between HLA-B*15:02 and the development of carbamazepine-induced SJS was first described among Han Chinese [71]. Several other studies have provided evidence to strengthen this association, which has been found in other Asian ethnicities such as Thai, Korean, Malay, and Indian populations, but not Japanese [70]. In a European case-control study including 12 carbamazepine-induced SJS/TEN cases, however, only 4 patients (all of Asian ancestry) were HLA-B*15:02 positive [72].…”
Section: Carbamazepinementioning
confidence: 98%
See 3 more Smart Citations
“…In fact, the association between HLA-B*15:02 and the development of carbamazepine-induced SJS was first described among Han Chinese [71]. Several other studies have provided evidence to strengthen this association, which has been found in other Asian ethnicities such as Thai, Korean, Malay, and Indian populations, but not Japanese [70]. In a European case-control study including 12 carbamazepine-induced SJS/TEN cases, however, only 4 patients (all of Asian ancestry) were HLA-B*15:02 positive [72].…”
Section: Carbamazepinementioning
confidence: 98%
“…Many HLA alleles associated with carbamazepine-induced SCAR have been identified, and the strongest associations have been reported for HLA-B*15:02 and HLA-A*31:01 [70]. Carriers of these alleles are mainly of South Asian ancestry.…”
Section: Carbamazepinementioning
confidence: 99%
See 2 more Smart Citations
“…One meta-analysis indicated that the association of HLA-A * 3101 with CBZ-induced HSS (OR = 13.2) was stronger than with SJS/TEN (OR = 3.94) [27]. Another comprehensive meta-analysis including more studies suggested that HLA-A * 3101 was a universal risk marker, irrespective of cutaneous ADR type [SJS/TEN: p = 4.03 × 10 -6 , OR (95% CI) = 5.65 (2.70-11.78); HSS/MPE: p = 4.46 × 10 -22 , OR (95% CI) = 8.58 (5.55-13.28)] [33]. …”
Section: Pharmacogenomics Study Of Drug-induced Sjs/ten: Association mentioning
confidence: 99%